Educational Attainment, Crime, and Causality: a Population-wide Sibling-based Design - van de Weijer, Steve G. A. (Journal of developmental and life-course criminology, 2024)
Criminologists have been interested in educational attainment for decades, a focus the field shares with virtually all other social and psychological sciences. The effects of formal schooling are expected to emerge across a host of developmental outcomes, but they are thought to be of particular relevance when assessing the risk of delinquency and crime. As time spent in formal schooling increases, the future risk of criminal offending is expected to fall precipitously. Associations between education and criminal outcomes have emerged repeatedly in the past, but evidence of causal effects remains in short order by comparison. In this study, register data from the Netherlands is used to examine the effects of educational attainment on offending in both adolescence and early adulthood. Using a population-wide discordant sibling design, our results are consistent with an argument that both education exposure and educational performance exert causal influences on criminal involvement. Until additional work of a similar nature is carried out, however, stronger assertions about the causal effects of education and crime remain premature.